2020
DOI: 10.3390/genes11101144
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of ABCG2 Genetic Variation in the Polish Population and Its Inter-Population Comparison

Abstract: ATP-binding cassette sub-family G member 2 (ABCG2), also known as breast cancer resistance protein (BCRP), is one of the key efflux ATP-binding cassette (ABC) transporters of xenobiotics, their metabolites and endogenous compounds such as urate. Some of its genetic variants have been found to influence protein functioning, resulting in serious clinical implications concerning chemotherapy response, as well as gout or blood group phenotype Jr(a-). Previous reports have suggested that the frequencies of certain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
1
1
0
Order By: Relevance
“…Reduced expression of transporter protein is seen in several tissues as a result of the ABCG2 c.421 C/A polymorphism, which makes ABCG2 protein unstable, especially in the endoplasmic reticulum, thus increasing the vulnerability to denaturation (Furukawa et al, 2009;Kobayashi et al, 2005;Prasad et al, 2013;Tanaka et al, 2015). Our investigation found that the prevalence of the ABCG2 34G/A polymorphism in our healthy control group differed when compared with studies done by Bäckström et al (2003), Bosch et al (2005), however, it is comparable with studies conducted by Fischer et al (2007), Lee, Jeong, et al (2007), Słomka et al (2020), Wang et al (2004), Wang et al (2007). ABCG2 421AA and 34AA genotypes showed an elevated risk for advancement of HIV disease when patients with HIV infection were compared with healthy subjects (p = 0.49, OR: 2.49; p = 0.38, OR = 2.35).…”
Section: Discussionsupporting
confidence: 77%
“…Reduced expression of transporter protein is seen in several tissues as a result of the ABCG2 c.421 C/A polymorphism, which makes ABCG2 protein unstable, especially in the endoplasmic reticulum, thus increasing the vulnerability to denaturation (Furukawa et al, 2009;Kobayashi et al, 2005;Prasad et al, 2013;Tanaka et al, 2015). Our investigation found that the prevalence of the ABCG2 34G/A polymorphism in our healthy control group differed when compared with studies done by Bäckström et al (2003), Bosch et al (2005), however, it is comparable with studies conducted by Fischer et al (2007), Lee, Jeong, et al (2007), Słomka et al (2020), Wang et al (2004), Wang et al (2007). ABCG2 421AA and 34AA genotypes showed an elevated risk for advancement of HIV disease when patients with HIV infection were compared with healthy subjects (p = 0.49, OR: 2.49; p = 0.38, OR = 2.35).…”
Section: Discussionsupporting
confidence: 77%
“…The amino acid substitution in the ALAD gene (Lys59Asn) leads to a more electronegative charge of the variant enzyme, which could alter binding affinities ( Onalaja and Claudio, 2000 ). The missense mutation of ABCG2 (Gln141Lys) is associated with reduced ABCG2 expression ( Slomka et al, 2020 ). The placental passage of PFOS and PFOA, however, has been shown to not depend on ABCG2 in a human placental perfusion model ( Kummu et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%